Elucidating the degradation mechanism of beef myofibrillar proteins under hydroxyl radical oxidation through the lens of cysteine oxidation modifications - Jiale Li; Jun Liu; Hui Yue; Yuanyuan Ma; He Li; Yuanliang Hu; Xiang Yu; Weiwei Dong; Yanli Feng (Food Chemistry: X)
The study aimed to assess the oxidative modification behavior of bovine myofibrillar proteins (MPs) cysteines (Cys) by hydroxyl radical (·OH) through the construction of an in vitr Fenton reaction system. The ·OH generated by the Fenton reaction induced large-scale oxidative modification of Cys, and redox proteomics identified a total of 1192 differential oxidation sites (Dos), 59 Dos were located in the MPs structure. The Cys of actin (17 Dos), myosin/myomesin (16 Dos), tenascin (12 Dos) and sarcomere (10 Dos) in the MPs structure showed active oxidative modification behavior towards ·OH, especially with the “-C-X-X-X-X-W-” structure amino acid sequence showed high sensitivity. Notably, the oxidative modification of Cys by ·OH was an irreversible process, as evidenced mainly by a significant decrease (p < 0.05) in protein sulfhydryl groups and unfolding of protein secondary and tertiary structures. While the intermolecular forces of MPs were altered, with the most direct result being the degradation of MPs, which had a positive effect on beef tenderness and a negative effect on water-holding capacity.